Conservation agriculture based practices sustains productivity and profitability and improves health of black calcareous soils under groundnut based production systems: Conservation agriculture based practices sustains productivity and profitability and improves health of black calcareous soils under groundnut based production systems - RAM A JAT; RAJARAM CHOUDHARY; KIRAN K REDDY (Journal of Oilseeds Research, 2023)
A field experiment was conducted during 2015 to 2019 at Research Farm of ICAR- Directorate of Groundnut Research, Junagadh, India to study the effects of tillage and residue management practices in two groundnut-based cropping systems. It could be concluded that minimum tillage along with residue application has the potential for higher system productivity, profitability, and improve the soil health.